Insulin resistance and oxidative stress in familial combined hyperlipidemia - Martinez-Hervas, Sergio; Fandos, Marta; Real, Jose T.; Espinosa, Olga; Chaves, F. Javier; Saez, Guillermo T.; Salvador, Amparo; Cerdá, Concha; Carmena, Rafael; Ascaso, Juan F. (Atherosclerosis, 2008)
Oxidative stress is associated with atherosclerosis. Familial combined hyperlipidemia (FCH) is considered as a human model of primary dyslipidemia and atherosclerosis frequently associated with insulin resistance (IR), but there are few data on its possible relation to oxidative stress. The objective of this study was to evaluate oxidative stress status using different markers in subjects with FCH assessing its possible correlation with anthropometric parameters and IR. This was a cross-sectional study. A cohort of 40 FCH patients (20 with IR (HOMA ≥ 3.2) and 20 without IR (HOMA < 3.2)), and 20 healthy volunteers were included, all of them non-diabetic, normotensive and non-smokers. We measured lipid profile, glucose and insulin levels in plasma, HOMA, and representative indicators of oxidative stress such as 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxo-dG), reduced glutathione (GSH), oxidized glutathione (GSSG) and GSSG/GSH ratio in mononuclear cells. All parameters were determined at basal conditions with standard methodology in the three groups. All FCH subjects showed an increased status of oxidative stress compared to the control group. When the impact of IR was investigated, significant differences between groups were observed in terms of increased levels of 8-oxo-dG, GSSG and GSSG/GSH ratio in FCH subjects with IR indicating higher levels of oxidative stress in these patients. Correlation studies showed that 8-oxo-dG and GSSG/GSH ratio are independently related to IR with odds ratio of 3.5 and 7.4, respectively. We conclude that FCH is related to oxidative stress, especially in the presence of IR.